Management of Food Security Culturization in Nature Elementary Schools: Policy, Learning, and Student Engagement - Hadiana, Deni; Sylvia, Novi; Salman, Ibnu; Permatasari, Anggraeni Dian; Alia, Nur; Saliem, Handewi Purwati (Mimbar Sekolah Dasar, 2024)
Food insecurity affects every aspect of student development. Cultivating food security through education can be implemented through the culturization of food security in nature schools, and it is encouraged to be managed at the elementary level. Research relating to differences in the influence of nature school management on food security has not yet been found. This research aims to analyze the differences in the influence of general and Islamic school management on the culturization of food security. This research used a quantitative approach with a multivariate analysis of variance method using SPSS software. Data were collected using questionnaires of 20 items consisting of three aspects: school policy, learning activity, and student engagement. The participants were 28 principals and representatives in 15 nature elementary schools in West Java Province, Indonesia. The respondents were chosen from a population of nature elementary school principals using purposive sampling. The sampling encompasses the distribution of nature elementary schools based on types of school management and their distributive location. The result of the multivariate test shows a value of 0,260 0.05. This result means that different types of school management have an insignificant impact on the culturization of food security. The weakest aspect is school policy, with a mean score of 15.93, while learning activity and student engagement obtain a mean score of 27.25 and 27.50 for each. These findings imply that school policy in nature elementary schools must be improved to support a food security culture.